2008
DOI: 10.1021/ic801388a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Dinuclear Iron(II) Spin Crossover Complex with Wide Hysteresis

Abstract: The magnetic properties and results from X-ray structure analysis for a new pair of iron(II) spin-crossover complexes [FeL1(meim) 2](meim) ( 1(meim)) and [Fe 2L2(meim) 4](meim) 4 ( 2(meim) 4), with L1 being a tetradentate N 2O 2 (2-) coordinating Schiff-base-like ligand [([3,3']-[1,2-phenylenebis(iminomethylidyne)]bis(2,4-pentane-dionato)(2-)N,N',O (2),O (2)'], L2 being an octadentate, dinucleating N 2O 2 (2-) coordinating Schiff-base-like ligand [3,3',3'',3''']-[1,2,4,5-phenylenetetra(iminomethylidyne)]tetra(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 24 publications
5
44
0
Order By: Relevance
“…Discontinuous spin transitions were recently associated with order/disorder transitions of counter ions 25 or additional ligand molecules 26 in the crystal packing. The order/disorder transition at a certain temperature facilitated a significant increase in the number of intermolecular contacts below this Hydrogen atoms were omitted for clarity.…”
Section: Structural Descriptionsmentioning
confidence: 99%
“…Discontinuous spin transitions were recently associated with order/disorder transitions of counter ions 25 or additional ligand molecules 26 in the crystal packing. The order/disorder transition at a certain temperature facilitated a significant increase in the number of intermolecular contacts below this Hydrogen atoms were omitted for clarity.…”
Section: Structural Descriptionsmentioning
confidence: 99%
“…1.5·cm 3 ·K mol −1 at 379 K. Then, the χMT value further decreases gradually to reach ca. 0.5 cm 3 ·K·mol −1 at 300 K. The critical temperatures of the warming (Tc↑) and cooling (Tc↓) modes in the abrupt spin transition area are 485 and 401 K, respectively, indicating the occurrence of ΔT = 84 K, which is the widest thermal hysteresis loop in the dinuclear system reported so far [26][27][28][29]33,34,48]. It is also noteworthy that the Tc↑ of 1·AsF6 is considerably higher than that of the related ethylene-bridged helicate [Fe II 2(L2 C2 )2](PF6)4·5H2O·MeCN (Tc↑ = 437 K) [34] by about 48 K. …”
Section: Magnetic Property Of 1·asf6mentioning
confidence: 83%
“…In one of these studies, we reported the SCO iron(II) dinuclear double helicate for the first time [34]. This compound, with the formula [Fe II 2 (L2 C2 ) 2 ](PF 6 ) 4 ·5H 2 O·MeCN, has two bis-tridentate type ligand strands (L2 C2 ) in which two 1,2,3-triazolimine moieties of the ligand strand are bridged by an ethylene chain (Scheme 1), and shows an anomalous two-step SCO with 11 K-wide hysteresis in a second step centered at 432 K, which is the highest hysteretic transition temperature in the dinuclear SCO system reported so far [26][27][28][29]33,48].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…↓ is strongly lattice-dependent. It is mediated and controlled by the elastic interactions between SCO-active centers in the crystal structure [11][12][13][14], and should be controllable by a process of rational materials design and synthesis [15][16][17].…”
Section: Introductionmentioning
confidence: 99%